Shadowhouse fall - Older, Daniel José (Older, Daniel José. Shadowshaper cypher, 2017)
Sierra and her friends are happy to live as shadowshapers. But a new beast called the Hound of Light will give them a run for their money. In this second volume of the Shaowshaper Cypher series, Sierra and her African and Latin American friends continue to face paranormal monsters as well as the beasts of prejudice and racism that run rampant on the streets of Brooklyn and in the hallways of their high school.